Sustainable forest management and West Malaysian sawntimber supply analysis - Abdul Samad, Abdul Rahim; Othman, Mohd Shahwahid (Canadian Center of Science and Education, 2009)
This paper examines the dynamic effects of sustainable forest management (SFM) on the West Malaysian sawntimber supply. Both short-run and long-run effects on sawntimber supply are studied using a multivariate cointegration analysis. The proxy of SFM variable is permanent forest reserve. It is expected as an exogenous negative shock in the sawntimber supply. In general, given the fact that West Malaysian sawntimber supply is decreasing since 1990s, the results show that sawntimber supply is statistically influenced by SFM practices. Furthermore, reducing of harvested area of forest has significant effect on sawntimber supply decreases. While in the short-run, the results suggest that there are negative impacts of SFM practices on sawntimber supply at 10 percent significant level, in the long-run, the result is significant at 1 percent level. This may to some extent pull down the West Malaysian sawntimber supply together by bringing the forest harvests to sustainable level.